Effect of Machined Surface Integrity on Fatigue Performance of Metal Workpiece: A Review - Guoliang Liu (SpringerOpen, 2021)
Abstract Fatigue performance is a serious concern for mechanical components subject to cyclical stresses, particularly where safety is paramount. The fatigue performance of components relies closely on their surface integrity because the fatigue cracks generally initiate from free surfaces. This paper reviewed the published data, which addressed the effects of machined surface integrity on the fatigue performance of metal workpieces. Limitations in existing studies and the future directions in anti-fatigue manufacturing field were proposed. The remarkable surface topography (e.g., low roughness and few local defects and inclusions) and large compressive residual stress are beneficial to fatigue performance. However, the indicators that describe the effects of surface topography and residual stress accurately need further study and exploration. The effect of residual stress relaxation under cycle loadings needs to be precisely modeled precisely. The effect of work hardening on fatigue performance had two aspects. Work hardening could increase the material yield strength, thereby delaying crack nucleation. However, increased brittleness could accelerate crack propagation. Thus, finding the effective control mechanism and method of work hardening is urgently needed to enhance the fatigue performance of machined components. The machining-induced metallurgical structure changes, such as white layer, grain refinement, dislocation, and martensitic transformation affect the fatigue performance of a workpiece significantly. However, the unified and exact conclusion needs to be investigated deeply. Finally, different surface integrity factors had complicated reciprocal effects on fatigue performance. As such, studying the comprehensive influence of surface integrity further and establishing the reliable prediction model of workpiece fatigue performance are meaningful for improving reliability of components and reducing test cost.